PENERAPAN MODEL SSCS PROBLEM SOLVING DENGAN METODE HYPNOTEACHING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA - Ahmad Dimyati (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2019)
The research was based on concerns about the development of mathematical critical thinking and mathematical communication ability. The purpose of this study was review and compare the differences of enhancing mathematical critical thinking ability between junior high school students who acquire Model of Search, Solve and Share (SSCS) through hypnoteaching method and those who acquire the conventional learning. This study was a quasi-experimental research with non-equivalent control group design consists of classroom experiments which obtain Model of Search, Solve and Share (SSCS) through hypnoteaching method and control class which obtain conventional learning. The population of this study is junior high school students in Tangerang, where the samples are the grade 8th students in one of the state junior high school in Tangerang. Instruments used to collect data in this research consists of mathematical critical thinking test instruments, student’s attitude scale, and observation sheets. The data obtained is analyzed using the mean difference test, which are the t-test, Mann-Whitney, and Rank-Spearman test. The results showed that the enhancement student’s mathematical critical thinking ability who gotten model os Search, Solve, Create, and Share (SSCS) through hypnoteaching method is better than who gotten conventional learning.